Development and characterization of a 68Ga-labeled A20FMDV2 peptide probe for the PET imaging of αvβ6 integrin-positive pancreatic ductal adenocarcinoma. Issue 1 (1st January 2020) - Ui, Takashi; Ueda, Masashi; Higaki, Yusuke; Kamino, Shinichiro; Sano, Kohei; Kimura, Hiroyuki; Saji, Hideo; Enomoto, Shuichi
Graphical abstract: Abstract: Pancreatic ductal adenocarcinoma (PDAC) is known to be one of the most lethal cancers. Since the majority of patients are diagnosed at an advanced stage, development of a detection method for PDAC at an earlier stage of disease progression is strongly desirable. Integrin αV β6 is a promising target for early PDAC detection because its expression increases during precancerous changes. The present study aimed to develop an imaging probe for positron emission tomography (PET) which targets αV β6 integrin-positive PDAC. We selected A20FMDV2 peptide, which binds specifically to αvβ6 integrin, as a probe scaffold, and 68 Ga as a radioisotope. A20FMDV2 peptide has not been previously labeled with 68 Ga. A cysteine residue was introduced to the N -terminus of the probe at a site-specific conjugation of maleimide-NOTA (mal-NOTA) chelate. Different numbers of glycine residues were also introduced between cysteine and the A20FMDV2 sequence as a spacer in order to reduce the steric hindrance of the mal-NOTA on the binding probe to αVβ6 integrin. In vitro, the competitive binding assay revealed that probes containing a 6-glycine linker ([ nat Ga]CG6 and [ nat Ga]Ac-CG6) showed high affinity to αVβ6 integrin. Both probes could be labeled by 67/68 Ga with high radiochemical yield (>50%) and purity (>98%). On biodistribution analysis, [ 67 Ga]Ac-CG6 showed higher tumor accumulation, faster blood clearance, and lower accumulation in the surrounding organs of pancreas than did [ 67 Ga]CG6. The αV β6 integrin-positive xenografts were clearly visualized by PET imaging with [ 68 Ga]Ac-CG6. The intratumoral distribution of [ 68 Ga]Ac-CG6 coincided with the αV β6 integrin-positive regions detected by immunohistochemistry. Thus, [ 68 Ga]Ac-CG6 is a useful peptide probe for the imaging of αV β6 integrin in PDAC.